The effect of concussion history on cognitive-motor integration in elite hockey players. (6th September 2016) - Hurtubise, Johanna; Gorbet, Diana; Hamandi, Yehyah; Macpherson, Alison; Sergio, Lauren
Aim: To observe the effects of concussion history on cognitive-motor integration in elite-level athletes.Methods: The study included 102 National Hockey League draft prospects (n = 51 concussion history [CH]; n = 51 no history [NC]). Participants completed two computer-based visuomotor tasks, one involved 'standard' visuomotor mapping and one involved 'nonstandard' mapping in which vision and action were decoupled.Results: We observed a significant effect of group on reaction time (CH slower) and accuracy (CH worse), but a group by condition interaction only for reaction time (p < 0.05). There were no other deficits found. We discussed these findings in comparison to our previous work with non-elite athletes.Conclusion: Previously concussed elite-level athletes may have lingering neurological deficits that are not detected using standard clinical assessments.